Synergistic enhancing of micellization and thermodynamic properties of some Gemini cationic surfactants related to benzo[d]thiazol-3-ium bromide - Farid I. El-Dossoki; Mohamed A. Migahed; Mahmoud M. Gouda; Samir A. Abd El-Maksoud (BMC Chemistry)
Abstract Herrin, three Gemini cationic surfactants related to benzo[d]thiazol-3-ium bromide with variable hydrocarbon chain lengths (TBC n = 6, 12, and 18) were synthesized successfully and confirmed by using IR and 1HNMR spectroscopies. Critical micelle concentration and different thermodynamic properties of all surfactants under study were measured using conductivity, density, molal volume, and refractive index techniques. The Critical micelle concentration of TBC 6, TBC 12, and TBC 18 surfactants measured from the different techniques shows an acceptable agreement. The molecular weight of the investigated surfactants was decreased with the order: TBC 18 > TBC 12 > TBC 6. An increase in the magnitudes of the association constant, Gibbs free energy of micellization, molar refraction, polarizability, and binding constant proved the effect of hydrocarbon chain length on increasing surfactant’s micellization as follows: TBC 18 < TBC 12 < TBC 6. The enhancement in surfactant properties was also indicated under the effect of different concentrations of inorganic salts (NaI, NaBr, NaCl, MnCl2, CuCl2, and CoCl2). This effect was measured using conductivity and refractive index measurements. Different salts were indicated to adsorb on head groups of micelles, leading to an increase in the degree of ionization of the surfactant solution and improved aggregation of the surfactant at lower concentrations. The increase in the negative value of Gibbs free energy of association in the presence of salts proved an increase in the stability of micelles formed in a 15% DMSO-water solvent at 298.15 K.